Determining code choice: written slogans during Egyptian revolution-January 2011 - Amin, Hanzada Hesham (AUC Knowledge Fountain, 2013)
This qualitative study aims at depicting the phenomenon of the written code switching between Modern Standard Arabic (MSA) and Egyptian colloquial Arabic (ECA) in the written slogans during the Egyptian revolution January 2011. Findings show that ECA clauses comprise a significant percentage as observed from the survey done through the questionnaire and application of Myers-Scotton's (1993) theoretical framework of Matrix Language Frame (MLF). These findings shed light on 1) Merging between MSA and ECA is a distinctive feature in Arabic in many domains 2)The best ways to benefit from this phenomenon in AFL teaching 3)The importance of the event in documenting the Arabic language and its varieties in face of future language change;and 4) Building on Bassiouney's (2010) idea that code switching and role are related, this thesis demonstrates that the protestors chose ECA code when they wanted to express their anger and embrace their new role or identity as having power over the regime.